Training of Cadres In The Context of Emergency Identification of Pregnant Women During The Covid 19 Pandemic (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The Covid-19 pandemic has changed many things, including the policy direction for the schedule of examinations for pregnant women, which was initially at least four times during pregnancy to one time, as long as the pregnancy is not problematic. In the midst of the COVID-19 pandemic, many pregnant women are reluctant to check their pregnancy at the hospital for fear of contracting the Corona virus, even though pregnancy checks still need to be carried out regularly. The purpose of this community service is to provide training to health cadres regarding emergencies in pregnancy so that cadres can provide assistance in order to identify emergency conditions during pregnancy during the COVID-19 pandemic. The method of activities carried out is cadre training and assistance to pregnant women. The results showed that after the training activities, the level of knowledge of cadres on emergency services in pregnant women increased and pregnant women in the high risk category were 53.7%. In conclusion, this community service program has succeeded in increasing the knowledge of cadres in assisting pregnant women during the COVID-19 pandemic.